Forgotten Forest Installation - Auzani Zeda, Mohamed Kassim; Endang, Lestari (2018)
The installation is inspired by the massive development issues the tropical rainforest ecosystems in Borneo and other parts of the world are facing. Human activity today destroys elements present in this rainforest via illegal logging, mining, and plantation, to name a few. These are all destructive investing activities that sometimes no longer put forward the principles of sustainability and balance. It is estimated that every day numerous species become extinct due to the destruction of this tropical rainforest ecosystem.